The Novel Psychoactive Substances in the UK Project: empirical and conceptual review work to produce research recommendations - Noreen D Mdege; Nick Meader; Charlie Lloyd; Steve Parrott; Jim McCambridge (NIHR Journals Library, 2017)
Background: Although illegal drug use has largely been declining in the UK over the past decade, this period has witnessed the emergence of a range of novel psychoactive substances (NPS) ('legal highs'). These are new, mostly synthetic, substances that mimic the effects of existing drugs). Despite there being many causes for concern in relation to NPS, there has been little prior study of the burden associated with their use in public health terms. Clarity is lacking on research priorities in this rapidly developing literature. Objectives: To inform the development of public health intervention research on NPS by reviewing existing data on their use, associated problems and potential responses to such problems. Design: A scoping review and narrative synthesis of selected bodies of evidence was undertaken to summarise and evaluate what is known about NPS use and the related harms of, and responses to, such use. Relevant literature was identified from electronic databases (covering January 2006 to June 2016 inclusive), Google (Google Inc., Mountain View, CA, USA), relevant websites and online drug forums and by contacting experts. Articles were included if they were primary studies, secondary studies involving the analysis and interpretation of primary research or discussion papers. A conceptual framework postulating an evidence-informed public health approach to NPS use in the UK was developed through a pragmatic literature review, the iterative development of concepts and finalisation in light of the results from the empirical review work. The process also involved feedback from various stakeholders. Research recommendations were developed from both strands of work. Results: A total of 995 articles were included in the scoping review, the majority of which related to individual-level health-related adverse effects attributable to NPS use. The prevalence of lifetime NPS use varied widely between (e.g. with higher prevalence in young males) and within population subgroups. The most commonly reported adverse effects were psychiatric/other neurological, cardiovascular, renal and gastrointestinal manifestations, and there is limited evidence available on responses. In these and other respects, available evidence is at an early stage of development. Initial evidence challenges the view that NPS should be treated differently from other illicit drugs. The conceptual framework indicated that much of the evidence that would be useful to inform public health responses does not yet exist. We propose a systems-based prevention approach that develops existing responses, is multilevel and life course informed in character, and emphasises commonalities between NPS and other legal and illegal drug use. We make 20 recommendations for research, including nine key recommendations. Limitations: Scoping reviews do not interrogate evidence in depth, and the disjunction between the scoping review and the conceptual framework findings is worthy of careful attention. Conclusions: Key research recommendations build on those that have previously been made and offer more evidence-based justification and detail, as previous recommendations have not yet been acted on. The case for decision-making on commissioning new research based on these recommendations is both strong and urgent. Future work: The validity of recommendations generated through this project could be enhanced via further work with research commissioners, policy-makers, researchers and the public. Study registration: The systematic review element of this study is registered as PROSPERO CRD42016026415. Funding: The National Institute for Health Research Public Health Research programme.